2010
DOI: 10.1007/s11626-010-9368-1
|View full text |Cite
|
Sign up to set email alerts
|

The H9C2 cell line and primary neonatal cardiomyocyte cells show similar hypertrophic responses in vitro

Abstract: Cardiac hypertrophy is a major risk factor for heart failure and associated patient morbidity and mortality. Research investigating the aberrant molecular processes that occur during cardiac hypertrophy uses primary cardiomyocytes from neonatal rat hearts as the standard experimental in vitro system. In addition, some studies make use of the H9C2 rat cardiomyoblast cell line, which has the advantage of being an animal-free alternative; however, the extent to which H9C2 cells can accurately mimic the hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
226
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(252 citation statements)
references
References 30 publications
(31 reference statements)
10
226
0
4
Order By: Relevance
“…These phenotypes are similar to previously reported cardiomyocyte hypertrophic responses in vitro. 13,[16][17][18] TGFb1 alone also stimulated comparable hypertrophic responses to those induced by Ang II treatment (Figures 1a-c), and in a similar way to a previous report. 19 Functional TGFb1 signaling is essential for the stimulation of cardiomyocyte hypertrophy by Ang II Immunoblot experiments showed that TGFb1 and AngII stimulated phosphorylation of Smad2 in PNCM cells (Figure 2a), in a similar way to previous reports.…”
Section: Ang II and Tgfb1 Induce Similar Hypertrophic Responses In Vitrosupporting
confidence: 91%
See 2 more Smart Citations
“…These phenotypes are similar to previously reported cardiomyocyte hypertrophic responses in vitro. 13,[16][17][18] TGFb1 alone also stimulated comparable hypertrophic responses to those induced by Ang II treatment (Figures 1a-c), and in a similar way to a previous report. 19 Functional TGFb1 signaling is essential for the stimulation of cardiomyocyte hypertrophy by Ang II Immunoblot experiments showed that TGFb1 and AngII stimulated phosphorylation of Smad2 in PNCM cells (Figure 2a), in a similar way to previous reports.…”
Section: Ang II and Tgfb1 Induce Similar Hypertrophic Responses In Vitrosupporting
confidence: 91%
“…2,12 We have previously shown that endothelin-1 and Ang II generated a very similar hypertrophic response in vitro. 13 Using this model we now show that Ang IIstimulated cardiomyocyte hypertrophy is dependent on TGFb receptor activity and requires the presence of TAK1, but not SMAD2/3.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Rat H9c2 cardiomyoblasts (American Type Culture Collection, Rockville, USA) were grown in DMEM media containing 10% heat‐inactivated FBS under 5% CO 2% and 95% air at 37°C. H9C2 served as an animal‐free alternative, sharing many physiological properties of primary cardiac cells (Watkins, Borthwick, & Arthur, 2011). Cells were transfected with MAO‐A siRNA, p53 siRNA or scramble siRNA (on‐target‐plus smart pool; Dharmacon) with DharmaFECT Duo (Dharmacon).…”
Section: Methodsmentioning
confidence: 99%
“…First, for the assessment of cell viability as a fundamental evaluation of cellular toxicity, we used H9c2 cells, which is a frequently used cardiac in vitro cellular model. The H9c2 cell line is derived from embryonic rat heart tissue and has been validated as a reliable model for its ability to mimic development and disease states [20]. Using this model, we uncovered the potential for DGA to decrease cell viability.…”
Section: Discussionmentioning
confidence: 99%